Vascular, Cognitive, and Psychomental Survey on Elderly Recycling Volunteers in Northern Taiwan - Chen, Guei-Chiuan; Chen, Pei-Ya; Su, Yu-Chin; Hsiao, Cheng-Lun; Yang, Fu-Yi; Hsu, Po-Jen; Lin, Shinn-Kuang (Frontiers in Neurology, 2019)
Background: Stroke and dementia represent frequent causes of psychophysical and socioeconomic burdens. We conducted a vascular, cognitive, and psychomental survey involving elderly volunteers at community-based recycling stations in Northern Taiwan. Methods: Recycling volunteers aged ≥60 years were surveyed. We recorded seven parameters, namely 1) body mass index (BMI), 2) fasting glucose, 3) fasting cholesterol, 4) ankle-brachial index (ABI), 5) carotid duplex sonography, 6) five-item Brief Symptom Rating Scale (BSRS-5) score, and 7) eight-item Interview to Differentiate Aging and Dementia (AD8). During the carotid duplex study, we measured the carotid intima-media thickness (CIMT) and the carotid total plaque score (CTPS) of the common and internal carotid arteries. Results: In total, 985 subjects (mean age: 70.8 years) participated in this study. Among these, 81% were women, and 52% were vegetarians. The average ABI, CIMT, and CTPS were higher in men, whereas women had higher cholesterol levels and BSRS-5 scores. Obesity, hypertension, hyperglycemia, and hyperlipidemia were present in 21%, 38%, 9%, and 27% of all subjects, respectively. Carotid plaques with mild (CTPS 1-5), moderate (CTPS 5.1-10), and severe (CTPS > 10) atherosclerosis were detected in 45%, 16%, and 7% of the subjects, respectively. Mild cognitive impairment (AD8 > 2) was observed in 13% of the subjects, whereas moderate mood disorder (BSRS-5 ≧10) was observed in only 1% of subjects. Vegetarians had a lower BMI, systolic blood pressure (SBP), cholesterol, CIMT, and CTPS than did nonvegetarians. Substantial predictors of severe atherosclerosis were advanced age (>70 years), male sex, history of heart disease, hyperlipidemia and currently elevated SBP and cholesterol levels. Predictors of mild cognitive impairment were illiteracy, history of hypertension, hyperlipidemia, and moderate mood disorder. Conclusions: Subclinical carotid atherosclerosis was common in elderly recycling volunteers, with 23% having moderate to severe stenosis. Vegetarians had a reduced risk of atherosclerosis. The low incidence of moderate mood disorder might indicate that recycling work enhances psychomental health. In addition, a healthier lifestyle, better mood condition, and vegetarian diet might contribute to lower incidence of mild cognitive impairment.